The Effect Red Betel Leaves (Piper Crocatum) On Pregnancy Gingivitis - Sandy Nurlaela Rachman; Fathiyati Fathiyati; Ade Anwar (Postgraduate, University of Mataram, 2024)
Gingivitis is a periodontal disease that easily occurs in pregnant women, such as inflammation of the gums (3). The decrease in pH in the mouth, the influence of the hormones estrogen and progesterone during pregnancy causes gum inflammation (4), so safe therapy is needed such as boiled water from red betel leaves which can improve the oral hygiene status of gingivitis sufferers (11) and the inhibitory power of red betel leaf extract is very potently inhibits microorganisms that cause periodontal disease (12). The aim of this study was to determine whether there is an effect of boiled water from red betel leaves (piper crocatum) on pregnancy gingivitis. The method used in this research is quasi experimental with a pretest-posttest with control group design. The sample studied was 60 pregnant women, consisting of 30 pregnant women in the treatment group and 30 pregnant women in the control group. Data analysis used the Independent T-test. The results of the case group research in the pretest were 15 people (50%) of pregnant women with gingivitis and 13 people (43.6%) in the moderate category, 6 people (20%) in the post test results after intervention without gingivitis and 21 people (70%) in the mild category. ), while in the control group in the pretest, 19 people (63.3%) had mild category of pregnant women with gingivitis, 9 people (30%) in the moderate category, 17 people (56.7%) in the post test after intervention in the mild category, moderate category 11 people (36.7%), as well as the influence of boiled water from red betel leaves (piper crocatum) on pregnancy gingivitis (pvalue 0.000 < 0.05). The conclusion is that boiled water from red betel leaves can reduce gingivitis so it can be used as a safe medicine to reduce gingivitis in pregnant women while maintaining oral and dental hygiene.